Nutrition Delivery Affects Outcomes in Pediatric Acute Respiratory Distress Syndrome. (9th March 2016) - Wong, Judith Ju‐Ming; Han, Wee Meng; Sultana, Rehena; Loh, Tsee Foong; Lee, Jan Hau
Abstract : Background: Malnutrition is prevalent in critically ill children. We aim to describe nutrition received by children with acute respiratory distress syndrome (ARDS) and to determine whether provision of adequate nutrition is associated with improved clinical outcomes. Materials and Methods: We studied characteristics and outcomes of 2 groups of patients: (1) those who received adequate calories (defined as ≥80% of predicted resting energy expenditure) and (2) those who received adequate protein (defined as ≥1.5g/kg/d of protein). Outcomes of interest were mortality, ventilator‐free days (VFDs), intensive care unit (ICU)–free days, multiorgan dysfunction, and need for extracorporeal membrane oxygenation. Categorical variables were analyzed using the Fisher exact test, and continuous variables were analyzed using the Mann‐Whitney U test. Univariate and multivariate logistic regression models were used to identify associated risk factors related to these outcomes of interest. Results: In total, 107 patients with ARDS were identified. There was a reduction in ICU mortality in patients who received adequate calories (34.6% vs 60.5%, P = .025) and adequate protein (14.3% vs 60.2%, P = .002) compared with those that did not. Patients with adequate protein intake also had more VFDs (median [interquartile range], 12 [3.0–19.0] vs 0 [0.0–14.8] days; P = .005). After adjusting for severity of illness, adequate protein remained significantly associated with decreased mortality (adjusted odds ratio [95% confidence interval], 0.09 [0.01–0.94]; P = .044). Conclusion: Our study demonstrated that adequate nutrition delivery in children with ARDS was associated with improved clinical outcomes. Protein delivery may have potentially more impact than overall caloric delivery.